Software Process Improvement: The Competisoft Project. - Oktaba, Hanna; García, Félix; Piattini, Mario; Ruiz, Francisco; Pino, Francisco J.; Alquicira, Claudia (Computer (00189162), 2007)
The article discusses the Competisoft project in Latin America. The project aims to help small software firms improve their image abroad, and promote efficient and effective software development processes. Existing guidelines for software development are more geared to larger companies and don't always take into account cultural considerations. Competisoft addresses competencies in process and project management, development, maintenance, business and resource management, evaluation, and improvement with the needs of small businesses in mind.